The Relationship between Professional Immigrant Parents’ Underemployment Status and their Children’s Emotional Health and Behavioral Patterns - Poureslami, Iraj; Hertzman, Clyde; Hattersley, Libby; Nimmon, Laura (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2010)
This study examined the relationship between a stressful life and low economical status due to underemployment among professional immigrants in the Greater Vancouver Area (GVA), and their children’s emotional and behavioural health. Employing a cross-sectional qualitative design, interviews and focus groups were conducted with the target population, and focus groups were held with representatives from immigrant service-provider agencies (key-informants). Findings were analysed according to participants’ employment status and country/region of origin. Underemployed participants reported the lowest levels of life satisfaction and health status for themselves and their families, the poorest family relationships and the most unfavourable emotional and behavioural patterns for their children. Southeast Asian participants reported the highest rates of underemployment and unfavourable child emotional and behavioural patterns, while the lowest rates in both categories were seen among Eastern European participants. The findings supported and expanded existing knowledge of the links between underemployment, family dysfunction, and poor child emotional and behavioural outcomes.